Truth and subjectivity in narrative inquiry: augmented reality & digital storytelling in the university classroom. Issue 2 (3rd April 2021) - Topouzova, Lilia
Abstract: In my university classroom teaching, I draw on my interdisciplinary background as both a humanistic scholar and a documentary filmmaker, presenting an approach to learning that integrates scholarship with a digital storytelling practicum. Questions that scrutinize the relationship between written and visual discourses, the possibilities and limits of each, inform both my research and pedagogical practices. Terms such as 'historiophoty' (White, 1988) and 'visionary history'(Rosenstone, 1988) were coined to describe the possibility of the study of history through film and images. The tensions embedded in these pioneering studies continue to animate current research and pedagogical discourses while raising pertinent questions. How can images help us learn about the past? Is it necessary for films to be historically accurate? I consider these questions and expand on anthropologist's John Jackson Jr's formulation of "what scholarship entails in our media age." I discuss my visual literacy pedagogical trajectory that culminated with a methodology I developed that merges elements of the academic and documentary film worlds, demonstrating the possibilities for interdisciplinary collaboration. This curriculum aims to visualize scholarly research and produce a digital media project that consists of technical and applied learning of the five stages of media production adapted for the university classroom.